1990
DOI: 10.1128/jb.172.3.1256-1261.1990
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, nucleotide sequence, and expression in Escherichia coli of the phospholipase D gene from Corynebacterium pseudotuberculosis

Abstract: The phospholipase D (PLD) gene from Corynebacterium pseudotuberculosis has been cloned, sequenced, and expressed in Escherichia coli. Analysis of DNA sequence data reveals a major open reading frame encoding a 31.4-kilodalton protein, a size consistent with that estimated for the PLD protein by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Comparison of these data with the amino-terminal protein sequence indicates that the mature PLD protein is preceded by a 24-residue signal sequence. Expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
1
6

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 19 publications
(16 reference statements)
1
38
1
6
Order By: Relevance
“…This protocol differs from those previously used to produce rPLD (25)(26)(27). Soluble rPLD was expressed using this protocol, in contrast with some other studies (25,27) but similar to the results reported by Songer et al (26). However, Songer et al found that the enzyme activity of the C. pseudotuberculosis culture supernatant was approximately 2.5-fold more effective than that of E. coli (pCpO5O).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…This protocol differs from those previously used to produce rPLD (25)(26)(27). Soluble rPLD was expressed using this protocol, in contrast with some other studies (25,27) but similar to the results reported by Songer et al (26). However, Songer et al found that the enzyme activity of the C. pseudotuberculosis culture supernatant was approximately 2.5-fold more effective than that of E. coli (pCpO5O).…”
Section: Discussioncontrasting
confidence: 53%
“…Differences have been noted between strains with respect to the amount of toxin and the size of the lesions (24). Various studies have characterized and examined the structure of natural and recombinant PLD exotoxins (7,21,25).…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipase D has been shown to play an important role in hematogenous dissemination of bacterial pathogens within infected animals and is considered a major virulence determinant of Corynebacterium pseudotuberculosis (1,13,34). Therefore, we hypothesized that PLD plays a role in A. baumannii pathogenesis and focused our effort on determining the in vitro and in vivo contributions of PLD to pathogenesis in the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, mammalian PLDs are recognized as key enzymes in intracellular signaling involved in processes such as inflammation, endocytosis, and cell shape changes (27), while bacterial PLDs from Corynebacterium pseudotuberculosis and Acinetobacter baumannii have been shown to be the critical virulence determinants of these organisms (25,29,44). In fungi, PLD appears to be closely related to fungal cell shape changes, such as sporulation in Saccharomyces cerevisiae (55) and the dimorphic transition of C. albicans (14).…”
mentioning
confidence: 99%